Cocitation or Capacity-Building? Defining Success within an Interdisciplinary, Sustainability Science Team - Roche, Abby J.; Rickard, Laura N. (Frontiers in Communication, 2017)
To address gaps in knowledge and to tackle complex social-ecological problems, scientific research is moving toward studies that integrate multiple disciplines and ways of knowing to explore all parts of a system. Yet, how these efforts are being measured and how they are deemed successful is an up-and-coming and pertinent conversation within interdisciplinary research spheres. Using a grounded theory approach, this study addresses how members of a sustainability science-focused team at a Northeastern U.S. university funded by a large, National Science Foundation (NSF) grant contend with deeply normative dimensions of interdisciplinary research team success. Based on semi-structured interviews (N = 24) with researchers (e.g., faculty and graduate students) involved in this expansive, interdisciplinary team, this study uses participants’ narrative accounts to progress our understanding of success on sustainability science teams and addresses the tensions arising between differing visions of success present within the current literature, and perpetuated by U.S. funding agencies like NSF. Study findings reveal that team members are forming definitions of interdisciplinary success that both align with, and depart from, those appearing in the literature. More specifically, some respondents’ notions of team success appear to mirror currently recognized outcomes in traditional academic settings (i.e., purpose driven outcomes – citations, receipt of grant funding, etc.). At the same time, just as many other respondents describe success as involving elements of collaborative research not traditionally acknowledged as a forms of “success” in their own right (i.e., capacity building processes and outcomes – relationship formation, deep understandings of distinct epistemologies, etc.). Study results contribute to more open and informed discussions about how we gauge success within sustainability science collaborations, forming a foundation for appreciation and exploration of the disciplinary and normative dimensions of this work.